Investor Limited Information Processing Capacity: Industry Level Analysis - Winston Sutandar; Angel Angel; Trixie Josunarto; John Iwan Kusno; Adrian Teja (Jurnal Manajemen dan Keuangan, 2019)
Investor has cognitive limitation in the form of limited information-processing capacity relative to the amount of information available to them. This limitation force investors to optimize their valuable resources by focusing only to a specific set of information based on their unique preference. Since different industry have different information complexities, different industries will have different investor segment in terms of investor number, investor sophistication, and investor speed to gather and to comprehend information from other industry. We investigate the prevalence of investor’s limited information-processing capacity in Indonesian stock market using autoregressive model. We used monthly data from 31 December 1999 to 30 September 2015 to identify whether there are industries that consistently lead other industries. We find only mining industry return, with small market capitalization only 3.3% relative to total Jakarta Composite Index market capitalization, which consistently leads Jakarta Composite Index return for one to two months.